THE MORPHO-FUNCTIONAL PECULIARITIES OF THE SYNSARCOSIS MUSCLES IN RED SQUIRRELS - Constantin SPATARU; Mihaela-Claudia SPATARU; Ozan GÜNDEMIR (Journal of Applied Life Sciences and Environment)
In terrestrial species, body propulsion is mostly performed via the pelvic limbs. In semiaquatic species, both pairs of limbs are used in swimming and diving, whereas in arboreal species, the pelvic limbs are used to maintain body stability. Thus, in squirrels, the synsarcosis muscles participate in body propulsion during climbing, as they have well-developed muscular bellies. Among these, the pectoral transverse muscle, which originates along the entire sternum and is inserted on the humeral crest, stands out for its width. The cervical parts of the trapezius and rhomboideus muscles are reduced and their thoracic parts more developed. As a result, muscles such as the occipitoscapularis or atlantoscapularis coordinate forelimb protraction and neck displacement. The serratus ventralis muscle is very well developed and clearly divided into cranial (cervical) and caudal (thoracic) parts; it produces a strong adduction of the thoracic limbs when the parts contract, and when they relax, a large abduction of the forelimbs is produced, enlarging the body size during jumping.